INFORMATION SYSTEM DESIGN FOR PURCHASE OF GOODS IN PT. MULTI GARMENT TAMA - Rini Astuti; Irfan Irfan, Skom, MM (Jurnal Sistem Informasi, 2001)
This scholarly writing explain about the design of information systems for dataprocessing in the process of buying goods at PT. Multi Garment Tama will be createdwith computer.In terms of data processing in the process of purchasing goods at PT. Multi GarmentTamamasih done manually. To the authors tried to modify and make an applicationprogramming for PT. Garment Multi Tama Tama.Where this information system design will be a problem in this scientific writing.Study Here the author will try and change this problem in the following manner:1. Analyzing maslaah of data processing is still done manually at the PT. MultiGarment Tama.2. Designing an application programming about the process of buying goods forPT. Tama in a computerized multi Garment desired.3. Making an application for subdivision simplification of work on the purchaseat. Multi Garment Tama and to reduce errors that occur, than if donemanually.Purchasing information system design begins with field research and ends withscientific writing, design of desired system will be created using DFD, ContextDiagram, Diagram Zero, ERD, Normalization, and also use programming languagesFoxPro.